Murder Among Brothers: The Deaths of Peter and Paul Reconsidered - Hansen, Chrissy M. (2024)
This article reevaluates 1 Clement 5.3–7 outside of the traditionally used backdrop of the Neronian persecution. Instead, finding the evidence for such a reading to be specious at best, especially as it pertains to the lives of Peter and Paul, an alternative interpretation is offered. Reinterpreting 1 Clement in the light of jealousy and internal tensions among early Christians, it is instead suggested that 1 Clement has in view a previous history where early Christians slew their own apostles Peter and Paul because of internal strife (which Clement blames specifically on jealousy/envy). This interpretation and explanation also has the benefit of explaining the inconsistency and lateness of the martyrdom traditions surrounding Peter and Paul, and likewise why other texts like Luke-Acts and John 21 are profoundly vague (in their attempt to ignore or embarrassingly silence these realities).
Keywords: Neronian persecution; martyrdom of Peter; martyrdom of Paul; 1 Clement